2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00623
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Source Weak Supervision for Saliency Detection

Abstract: The high cost of pixel-level annotations makes it appealing to train saliency detection models with weak supervision. However, a single weak supervision source usually does not contain enough information to train a wellperforming model. To this end, we propose a unified framework to train saliency detection models with diverse weak supervision sources. In this paper, we use category labels, captions, and unlabelled data for training, yet other supervision sources can also be plugged into this flexible framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 35 publications
0
119
0
Order By: Relevance
“…In greater detail, visual information is grouped into multi-cues vectors to discard the non-salient regions and highlight the salient area. Zeng et al [80] proposed a unified framework to train saliency detection models with diverse weak supervision sources to overcome issues characterizing saliency maps achieved with a single weak supervision source. Other very popular methods in [81], [82] and [83] are based on unsupervised approaches.…”
Section: ) Deep Neural Network Based Saliency Techniquesmentioning
confidence: 99%
“…In greater detail, visual information is grouped into multi-cues vectors to discard the non-salient regions and highlight the salient area. Zeng et al [80] proposed a unified framework to train saliency detection models with diverse weak supervision sources to overcome issues characterizing saliency maps achieved with a single weak supervision source. Other very popular methods in [81], [82] and [83] are based on unsupervised approaches.…”
Section: ) Deep Neural Network Based Saliency Techniquesmentioning
confidence: 99%
“…To alleviate this issue, there has been increasing interest in weakly and semi-supervised learning, which have been applied to salient object detection [185][186][187][188][189]. Semi-and weak supervision could also be introduced into RGB-D salient object detection, by leveraging image-level tags [185] and pseudo pixel-wise annotations [188,190], to improve detection performance. Furthermore, several studies [191,192] have suggested that models pretrained using self-supervision can effectively be used to achieve better performance.…”
Section: Different Supervision Strategiesmentioning
confidence: 99%
“…l , Ac h and Ac l ) and the scaling factor r in Equation (8). To determine these hyperparameters, we conduct several sets of experiments in Section 6.4.3.…”
Section: Ip H Ipmentioning
confidence: 99%
“…The PASCAL-S dataset contains 850 images with cluttered scenes and is one of the most challenging salient object FIGURE 8 Qualitative comparisons between our salient object detection approach and other state-of-the-art methods. From left to right (columns): input image, ground truth, Amulet [10], UCF [11], DRFI [40], MR [16], SO [18] and MBS [41], DSR [15], MWS [8] and ours detection datasets. The ECSSD dataset has 1000 images with complex structures.…”
Section: Datasets and Evaluation Metricsmentioning
confidence: 99%